Design and Qualification of Pr–Fe–Cu–B Alloys for the Additive Manufacturing of Permanent Magnets. (16th June 2021) - Schäfer, Lukas; Skokov, Konstantin; Liu, Jianing; Maccari, Fernando; Braun, Tobias; Riegg, Stefan; Radulov, Iliya; Gassmann, Jürgen; Merschroth, Holger; Harbig, Jana; Weigold, Matthias; Gutfleisch, Oliver
Abstract: The direct use of an advanced binder‐free additive manufacturing technique, namely laser powder bed fusion (L‐PBF), does not easily allow obtaining variously shaped, fully dense Nd–Fe–B magnets with high coercivity. The process inherently leads to the re‐melting of the powder and appearance/disappearance of undesired/desired microstructural features responsible for low and large coercivity. In this work, the development of a useful microstructure responsible for high coercivity in Pr21 Fe73.5 Cu2 B3.5 and Nd21 Fe73.5 Cu2 B3.5 alloys and a possible way to produce fully dense permanent magnets via additive manufacturing processes is demonstrated using: (i) suction casting technique, which provides a high cooling rate and thus similar microstructures as in L‐PBF but requires only very small amounts of powder; (ii) conventional L‐PBF processing using kg of powder, and (iii) a subsequent annealing treatment that is similar to a conventional sintering treatment. The subsequent heat treatment is necessary to develop high coercivity by forming a novel microstructure: hard magnetic (Nd, Pr)2 Fe14 B grains embedded in a matrix of intermetallic (Nd, Pr)6 Fe13 Cu phase. Furthermore, it is demonstrated that Pr21 Fe73.5 Cu2 B3.5 exhibits a higher coercivity than Nd21 Fe73.5 Cu2 B3.5 because of a finer and more homogeneous grain size distribution of the Pr2 Fe14 B phase. The final L‐PBF printed Pr21 Fe73.5 Cu2 B3.5 samples provide a coercivity of 0.75 T. Abstract : A new alloy and grain boundary design strategy to produce fully dense permanent magnets by additive manufacturing processes is proposed. After solidification of a Pr–Fe–Cu–B‐based alloy by laser powder bed fusion, the initial low coercivity due to an inappropriate microstructure is restored by temperature‐controlled phase transformation for efficient and stable magnetic hardening in 3D‐printed magnets.